"Political Atmospherics": The India Round Table Conference's Atmospheric Environments, Bodies and Representations, London 1930–1932. Issue 3 (3rd May 2020) - Legg, Stephen
Abstract : Between 1930 and 1932 the three sessions of the Round Table Conference in London drew more than seventy Indian delegates to the city, for up to three months, to debate India's constitutional future within the British Empire. This article argues that the atmosphere of the conference was central to its successes and failures and that studying atmospheres can help us think about the co-constitution of place, bodies, and politics more broadly. It approaches atmospheres from three interrelated perspectives. First, the atmospheric environment of the conference is set, in terms of both the physical geography of the weather and the human geography of the conference venue. Second, it traces conference bodies, which endured the weather, used it as metaphor, and attuned their politics to the affective atmosphere. The article concludes with reflections on representing non-representational atmospheres. It argues that the current atmospheres literature is oddly deraced, while debates about weather and bodies' reactions to social and political atmospheres are inherently and always racialized. Analyzing the reactions of and to diverse Indian delegates in 1930s London gives us insights into an interwar colonial geographical imagination and demonstrates the potential for thinking about meteorological and affective atmospheres together. Key Words: atmospheres, conferences, imperialism, India, race .